Sprinkler rotation and water application rate for the new type complete fluidic sprinkler and impact sprinkler - Dwomoh, Frank A.; Shouqi, Yuan; Hong, Li (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: One important indicator of the good performance of rotating sprinklers is the uniformity of rotation. The objective of this experimental study was to investigate the rotation uniformity and water application rate of the newly designed complete fluidic sprinkler in comparison to the widely used impact sprinkler, with the goal to offer recommendations to improve the fluidic sprinkler’s operation performance. Single-sprinkler water application experiments were conducted in accordance with the American Society of Agricultural and Biological Engineers standard. Sprinkler completion time through the four quadrants of rotation and water delivery in catch cans were measured at different operating pressures for each sprinkler-nozzle size configuration. The capabilities of Matrix Laboratory were employed to simulate the overlap of adjacent quadrants and to visualize the effect of sprinkler rotation speed variation on water application rate. Quadrant completion time variations were small for both impact and fluidic sprinklers. However, variations in completion time through the quadrants were higher for the fluidic sprinkler compared to the impact sprinkler. Relatively higher variations in water application rates were also observed for the fluidic sprinkler. The optimization of the design features of the fluidic component is necessary to improve rotation stability and to minimize variability in water application rate of the fluidic sprinkler. The study significantly highlighted some performance qualities of the complete fluidic sprinkler in comparison to that of the impact sprinkler. The findings of this research will help to improve the efficiency of the new type complete fluidic sprinkler.Keywords: sprinkler rotation, variation, water application rate, complete fluidic sprinkler, impact sprinkler, rotation uniformityDOI: 10.3965/j.ijabe.20140704.005Citation: Dwomoh F A, Yuan S Q, Li H. Sprinkler rotation and water application rate for the newly invented wall attachment fluidic sprinkler and impact sprinkler. Int J Agric & Biol Eng, 2014; 7(4): 38-46.